PERBEDAAN PENGARUH MODEL PEMBELAJARAN INQUIRY DAN MODEL PEMBELAJARAN DIRECT INTRUCTION TERHADAP PRESTASI BELAJAR SEJARAH DITINJAU DARI SEGI KEMANDIRIAN BELAJAR SISWA - Prakarti, Tania Rosafina; Herimanto, Herimanto; Musadad, Akhmad Arif (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
This study aims to find out; 1) the difference effect between Inquiry and Direct Intruction learning models toward learning achievement of history, 2) the difference effect between Inquiry land Direct instruction toward learning achievement history viewed from high learning independence, 3) the difference effect between Inquiry land Direct instruction toward learning achievement history viewed from low learning independence 4) the interaction effect between the model of learning and learning independence in learning of achievement of history.This study use a quantitative approach to experiment with factorial design 2 x 2. The population in this study were all students of class XI SMA Negeri 1 Kroya, Cilacap District, Central Java. The sampling technique used is the technique of simple random sampling, in this study the sample were students of class XI IPA 1 and XI IPA 2 SMA Negeri 1 Kroya. Data were collected by means of is test and questionnaires. Those data were analyzed with Two way Anava test with different content of cel, followed with multiplr comparison of Scheffe method with level of significance 0,05. Before analysis, Validity test conducted by Product Moment Correlation, reliability using Cronbach?s Alpha and KR 20 test for normality and homogenity test.The result of hypothesis show that (1) there were significance between Inquiry and Direct Intruction learning model toward learning achievement (Fhitung> Ftabel or 40.723>3.16). (2) the were significance between Inquiry land Direct instruction toward learning achievement history viewed from high learning independence (sig 0.000<0.05). (3) there were significance between Inquiry land Direct instruction toward learning achievement history viewed from low learning independence (sig.0.006<0.05). (4) there was no effect interaction between teaching with the independence learning towards their achievement of history (sig. 0,533 >0,05).